2020
DOI: 10.1002/prep.202000077
|View full text |Cite
|
Sign up to set email alerts
|

Function of a PETN‐Based Exploding Bridgewire Detonator Post Melt

Abstract: Exploding bridgewire (EBW) detonators are used for a variety of purposes and subjected to a wide range of conditions during transport and use, however, few studies have been conducted on stability at high temperatures. Many EBW's contain pentaerythritol tetranitrate (PETN) as the initiating explosive, which has been shown to exhibit a relatively low melt at 141°C, followed by an onset of decomposition of approximately 160°C. In the present work, we have evaluated the behavior of PETN with X-ray radiography in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The present work expands our understanding of detonator functionality in accidents involving high temperatures such as fires; specifically, in detonators that contain pentaerythritol tetranitrate (PETN) [10,11]. Manner et al [12] observed PETN melting in EBW detonators (with transparent sleeves) heated just above the melt temperature and held at those conditions for times ranging from 5-10 minutes. The detonators were positioned at various orientations with respect to gravity.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The present work expands our understanding of detonator functionality in accidents involving high temperatures such as fires; specifically, in detonators that contain pentaerythritol tetranitrate (PETN) [10,11]. Manner et al [12] observed PETN melting in EBW detonators (with transparent sleeves) heated just above the melt temperature and held at those conditions for times ranging from 5-10 minutes. The detonators were positioned at various orientations with respect to gravity.…”
Section: Introductionmentioning
confidence: 65%
“…Manner et al. [12] observed PETN melting in EBW detonators (with transparent sleeves) heated just above the melt temperature and held at those conditions for times ranging from 5–10 minutes. The detonators were positioned at various orientations with respect to gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the traditional thin brass sleeves, these detonators were supplied with clear plastic sleeves, allowing for visibility of the PETN during heating and firing. Unlike traditional RP-1 detonators, these modified RP-1’s are open at the top, allowing the output pellet to be visible …”
Section: Experimental Sectionmentioning
confidence: 99%
“…We also estimate the amount of decomposition relative to sublimation that we measure through gas evolution. As there has been recent interest in the performance of thermally damaged detonators, ,, we also characterize the performance through firing behavior of the molten PETN in commercial detonators. This is a critically important area of study as it influences the handling safety for detonators and other explosive systems which have been thermally compromised and will impact future safety qualifications.…”
Section: Introductionmentioning
confidence: 99%
“…The shape and material nature of Cu foil, which affects the energy deposition, plasma output ability and flyer velocity, is the most researched topic on exploding foil detonators [1][2][3], which are considered as the key materials for electronic safe and arm systems for rocket motor ignition, fuzing, ammunition, and flight termination applications [4][5][6][7][8][9][10][11][12]. The velocity and shape of the flyer are two key factors that affect the energy-output effect of exploding foil initiators.…”
Section: Introductionmentioning
confidence: 99%